1981
DOI: 10.1002/art.1780240723
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens in Mexican patients with adult rheumatoid arthritis

Abstract: LETTERSmeasure reflecting biologically important features of a crystal surface.These experiments confirm and extend Mandel's work. The results re-emphasize the problems inherent in all experimental work on crystal-induced inflammation; crystal structure and surfaces are clearly susceptible to widely used laboratory manipulations, and much previous work on "treated" crystals must be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…For example, in Caucasians (North Americans and Northern Europeans) the main alleles associated with RA are DRB1*0401, and DRB1*0404; while DRB1*0405 was found in Asians, the DRB1*0405 and *1001 in Spanish, and the DRB1*0102 in Israelis [26]. In addition, our study is in agreement with those of Gorodezky et al [27] and Debaz et al [28] who analyzed associations of HLA-DRB1 alleles with RA in Mexican Mestizos. Moreover, in the last study, the authors described an association between SEϩ (DRB1*0404) and RA as well as an association between SEϩ and presence and number of rheumatoid nodules as a manifestation of severity disease.…”
Section: Discussionsupporting
confidence: 95%
“…For example, in Caucasians (North Americans and Northern Europeans) the main alleles associated with RA are DRB1*0401, and DRB1*0404; while DRB1*0405 was found in Asians, the DRB1*0405 and *1001 in Spanish, and the DRB1*0102 in Israelis [26]. In addition, our study is in agreement with those of Gorodezky et al [27] and Debaz et al [28] who analyzed associations of HLA-DRB1 alleles with RA in Mexican Mestizos. Moreover, in the last study, the authors described an association between SEϩ (DRB1*0404) and RA as well as an association between SEϩ and presence and number of rheumatoid nodules as a manifestation of severity disease.…”
Section: Discussionsupporting
confidence: 95%
“…Most studies conducted in Mexico, from where MAs trace their ancestry, used serologic HLA-DR typing, and thus it was not clear whether RA in Mexicans was associated with the SE sequences (16,18,19). Most studies conducted in Mexico, from where MAs trace their ancestry, used serologic HLA-DR typing, and thus it was not clear whether RA in Mexicans was associated with the SE sequences (16,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies of the genetics of RA in Mexicans (16)(17)(18)(19)(20), and none in Mexican Americans (MAs; i.e., persons of Mexican ancestry living in the US). MAs are of interest for genetic studies because they are a hybrid population of European (Spanish) and Native American ancestries, with a smaller West African contribution (21)(22)(23).…”
mentioning
confidence: 99%
“…The analysis of class-I antigens did not reveal any meaningful association with RA. Since in most populations studied so far, RA has been correlated with DR4 (Stastny 1980, Ohta et al 1982, Sasazuki 1982, Gorodezky et al 1981, Karr et al 1980, we were mainly interested in the distribution of DR4 and the other DR antigens. In agreement with Schiff et al (1982), our sampl'e shows no association with DR4 in non-Ashkenazi patients and only a weak and non-significant increase of DR4 in Ashkenazi patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although an association of Rheumatoid Arthritis (RA) with HLA-DR4 has been confirmed in numerous studies involving Caucasoids (Stastny 1980, Japanese (Ohta et al 1982, Sasazuki 1982, Mexican (Gorodezky et al 1981) and American Black populations (Stastny 1980, Karr et al 1980, this association was not observed in immigrant Asian-Indians in the United Kingdom (Woodrow 1982), Yakima Indians in the USA (Willkens et al 1982) and in 49 Israeli Jewish patients (Schiff et al 1982). Failure to demonstrate an association between DR4 and RA in these specific ethnic groups raises questions as to the aetiologicai role of DR4 in determining susceptibility to RA.…”
mentioning
confidence: 99%